Exploring ‘place-based’ initiatives in philanthropic community development: A transnational examination of Canadian and US Foundations - and Newton, Josh; Rabinowitz Bussell, Mirle; Martinez-Cosio, Maria; Pole, Nancy; Fontan, Jean-Marc (Local Development & Society, 2024)
Though the concept of place-based philanthropy is common parlance in community development scholarship and practice, there is still uncertainty around its meaning due to the multidisciplinary nature of its study and definitional variation among and between scholars and practitioners. This article presents findings from a recently edited volume created by a binational research team. Ten cases of philanthropic initiatives were explored to develop a transnational understanding of foundation engagement in place-based philanthropy. Place-based philanthropy was explored by considering collaboration with other stakeholders, initiative evaluation, systems change efforts, and issues of power, equity, and justice. Our findings suggest that place-based philanthropy among foundations is heterogeneous. While some foundations adhere to traditional forms of place-based philanthropy, others are pushing the boundaries of this type of work. This article urges both academics and practitioners to reimagine place-based philanthropy for transformative purposes.
Keywords: Place-based philanthropy; community development; equity and justice; systems change; transnational study